Islam dan Pergolakan Politik Pada Era Orde Baru - Abdul Rahman (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2018)
This paper intends to present the pattern of relations between Islam and the Government in Orde Baru political stage. As is known that the emergence of the Orde Baru is inseparable from the main support of the TNI and civil society who are members of Islamic groups. As a group that has contributed to the establishment of Orde Baru, then of course there is a political adage "there is no free lunch". Islamic groups certainly hope to be involved in the political processes of the Orde Baru state which was commandeered by Suharto. However, these hopes must end in disappointment. Instead Islamic political groups enjoy political power, but instead must enjoy disappointment. Islamic groups have attempted to carry out political struggles on the Orde Baru stage, but their struggle is considered to be a threat to national stability so that the Orde Baru government exerted pressure and weakened the political power of Islam.